2011
DOI: 10.1242/dev.059451
|View full text |Cite
|
Sign up to set email alerts
|

Ribeye is required for presynaptic CaV1.3a channel localization and afferent innervation of sensory hair cells

Abstract: SUMMARYRibbon synapses of the ear, eye and pineal gland contain a unique protein component: Ribeye. Ribeye consists of a novel aggregation domain spliced to the transcription factor CtBP2 and is one of the most abundant proteins in synaptic ribbon bodies. Although the importance of Ribeye for the function and physical integrity of ribbon synapses has been shown, a specific role in synaptogenesis has not been described. Here, we have modulated Ribeye expression in zebrafish hair cells and have examined the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
182
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(197 citation statements)
references
References 36 publications
13
182
0
Order By: Relevance
“…Similar results, regarding mislocalized ribbons that do not form synapses, were reported in a transgenic zebrafish line overexpressing ribeye b (Sheets et al, 2011). Those results, as well as our findings, suggest that if hair cell presynaptic assembly is altered, either by overexpression of presynaptic components PCR product was sequence verified and used for in vitro transcription using the mMESSAGE mMACHINE T7 Ultra kit (Life Technologies) according to the manufacturer's instructions.…”
Section: Morpholino and Crna Injectionssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results, regarding mislocalized ribbons that do not form synapses, were reported in a transgenic zebrafish line overexpressing ribeye b (Sheets et al, 2011). Those results, as well as our findings, suggest that if hair cell presynaptic assembly is altered, either by overexpression of presynaptic components PCR product was sequence verified and used for in vitro transcription using the mMESSAGE mMACHINE T7 Ultra kit (Life Technologies) according to the manufacturer's instructions.…”
Section: Morpholino and Crna Injectionssupporting
confidence: 88%
“…The ribeye b antibody, developed and qualified by our laboratory (Fig. S5), showed the characteristic puncta staining at the base of the hair cells (Sheets et al, 2011) in controls (Fig. S5, A and C) but not hair cells (Söllner et al, 2004;Seiler et al, 2005).…”
Section: Clarin-1 Deficiency Affects Localization Of Synaptic Componentsmentioning
confidence: 99%
“…To address this question, we cotransfected COS cells, i.e., nonneuronal cells that do not contain synaptic ribbons, with full-length RIBEYE(AB)-and PAsensor protein constructs. Heterologously expressed full-length RIBEYE(AB) forms electron-dense protein aggregates Sheets et al, 2011) that resemble synaptic ribbons and that are denoted as artificial synaptic ribbons in the following text. For these COS cell experiments, we used mCherry-tagged Raf-1 as PA-sensor protein because Raf-1 does not require high intracellular Ca 2ϩ levels for PA binding, a situation that may not occur in COS cells (Gosh et al, 1996(Gosh et al, , 2003Baillie et al, 2002) (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The hierarchy of regulation is likely to differ between synapse formation and structural plasticity and among different synapses. Active zone size in sensory cells may additionally be governed by expression levels (Sheets et al, 2011) the effect of CAST/ERC2 deletion. Synapses were formed, showed a generally preserved molecular presynaptic and postsynaptic organization, and were functional.…”
Section: Reduced Active Zone Size But Preserved Molecular Synapse Anamentioning
confidence: 99%
“…The mechanisms regulating active zone size are not well understood but likely to involve Liprins/Syd proteins (Stigloher et al, 2011), cytomatrix of the active zone (CAZ) proteins, such as CAST/ELKS (Kittel et al, 2006), Bassoon and Piccolo (Zhai et al, 2000(Zhai et al, , 2001, and, at ribbon synapses, also RIBEYE (Sheets et al, 2011). Some synapses, such as the neuromuscular junction or ribbon synapses of photoreceptors, and hair cells use large active zones to accommodate high rates of synaptic transmission.…”
Section: Introductionmentioning
confidence: 99%